1981
DOI: 10.1094/pd-65-663
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Tomato Spotted Wilt Virus, the Causal Agent of Bud Necrosis of Peanut, byScirtothrips dorsalisandFrankliniella schultzei

Abstract: Tomato spotted wilt virus, the cause of bud necrosis of peanut, was transmitted by Scirtothrips dorsalis and Frankliniella schultzei. S. dorsalis is a new vector of the virus, but it is a less efficient vector than F. schultzei. Hemagglutination tests detected viral antigens in extracts from both thrips speSesexppsSa to ihffctedleavesT B ud necrosis is p ro b a b ly the m ost i m p o r t a n t v ir a l d is e a s e o f p e a n u t (A rachis hypogaea L.) in India (3,6). U ntil 1977, the v ecto r was unknow n,, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 6 publications
0
20
0
3
Order By: Relevance
“…dorsalis has been reported to transmit GBNV (Amin et al, 1981), but there is some doubt now as to the validity of this record (Palmer et al, 1990). S. dorsalis has been found to transmit Groundnut chlorotic fan-spot virus (GCFV) and Groundnut yellow spot virus (GYSV) .…”
Section: Scirtothrips Dorsalis Hoodmentioning
confidence: 99%
See 1 more Smart Citation
“…dorsalis has been reported to transmit GBNV (Amin et al, 1981), but there is some doubt now as to the validity of this record (Palmer et al, 1990). S. dorsalis has been found to transmit Groundnut chlorotic fan-spot virus (GCFV) and Groundnut yellow spot virus (GYSV) .…”
Section: Scirtothrips Dorsalis Hoodmentioning
confidence: 99%
“…S. dorsalis was reported as the least efficient vector. T. tabaci was found not to be a vector (Amin et al, 1981). However, S. dorsalis was found later not to be a vector and F. schultzei only transmitted the virus at a very low frequency (2%) in the laboratory (Lakshmi et al, 1995).…”
Section: Groundnut Bud Necrosis Virus (Gbnv)mentioning
confidence: 99%
“…Thrips vectors can include Frankliniella bispinosa (Webb et al 1998), F. intonsa (Wijkamp et al 1995), F. fusca, F. occidentalis, F. schultzei, Thrips palmi, T. setosus and T. tabaci. T. flavus (Singh and Krishnareddy 1996), F. tenuicornis (Kormelink 1994) and Scirtothrips dorsalis (Amin et al 1981) have been reported as vectors, but their status as such has yet to be confirmed.…”
Section: Life Cyclementioning
confidence: 99%
“…In this regard, DNA barcoding can be an added advantage and an effective tool for molecular species identification (Brunner et al 2004;Glover et al 2010; Lee et al 2010), elucidation of biotypes or cryptic species, and host associated genetic differences (Shufran et al 2000;Brunner et al 2004) and species discovery in insects. Additionally, DNA barcoding could also be used in the identification of unknown thrips species that co-exist in a cropping system, since one particular Tospovirus disease may sometimes be vectored by more than one species of thrips (Wijkamp et al 1995;Kadirvel et al 2013;Amin et al 1981). …”
Section: Advantages Of Dna Barcoding In Taxonomymentioning
confidence: 99%